2003
DOI: 10.1038/nrm1009
|View full text |Cite
|
Sign up to set email alerts
|

Nongenomic actions of steroid hormones

Abstract: Steroid hormones modulate many physiological processes. The effects of steroids that are mediated by the modulation of gene expression are known to occur with a time lag of hours or even days. Research that has been carried out mainly in the past decade has identified other responses to steroids that are much more rapid and take place in seconds or minutes. These responses follow nongenomic pathways, and they are not rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
533
2
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 807 publications
(557 citation statements)
references
References 111 publications
10
533
2
12
Order By: Relevance
“…We showed that estrogen rapidly induces c-Src activation via phosphorylation of Tyr 416, leading to the formation of the p-Src/ZO-1 complex at the cell membrane. This finding was consistent with previous reports showing that, in addition to its nuclear functions, ER also participates in extranuclear signaling events [30]. These events include the binding of ER beta to c-Src in prostate cancer cells [31]; the ER-Src axis constitutes a critical pathway used by breast cancer cells in the development of resistance [10].…”
Section: Discussionsupporting
confidence: 93%
“…We showed that estrogen rapidly induces c-Src activation via phosphorylation of Tyr 416, leading to the formation of the p-Src/ZO-1 complex at the cell membrane. This finding was consistent with previous reports showing that, in addition to its nuclear functions, ER also participates in extranuclear signaling events [30]. These events include the binding of ER beta to c-Src in prostate cancer cells [31]; the ER-Src axis constitutes a critical pathway used by breast cancer cells in the development of resistance [10].…”
Section: Discussionsupporting
confidence: 93%
“…The extracellular application of progesterone also rapidly triggers hyperactivated motility and initiation of the acrosome reaction [84][85][86][87][88][89][90][91]. Based on the fast activation rate, and fact that sperm cells are transcriptionally silent, it was believed that the nuclear progesterone receptor was not involved [85,88,[92][93][94][95]. However, direct evidence of the instantaneous, and therefore non-genomic, effect of this steroid only came with the discovery that progesterone acts on human sperm through potentiation of the CatSper channel [18,27] with EC 50 ∼ 7 nM [18].…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 99%
“…Alternate mechanisms have been proposed that rely on short-term, rapid cytoplasmic-based signaling effect initiated from the steroid receptor known as nonclassical or nongenomic steroid signals [11]. Nongenomic steroid signaling responses tend to be rapid, insensitive to inhibitors of mRNA and protein synthesis, lack nuclear-based steroid receptors, can be initiated by steroids coupled with high molecular weight substances such as estrogen-bovine serum albumin that do not permit transition across the plasma membrane, and are located in highly specialized cells (e.g., spermatozoa) that do not require mRNA and protein synthesis.…”
Section: Estrogen Signalingmentioning
confidence: 99%